Modeling and control simulation of a robotic chair-arm: protection against COVID-19 in rehabilitation exercise - Akhtaruzzaman, Md.; Shafie, Amir Akramin; Khan, Md. Raisuddin; Rahman, Md. Mozasser (Military Institute of Science and Technology (MIST), 2020)
In the field of rehabilitation, lower-limbs therapeutic exercise has become a challenging job for medical professionals in COVID-19 pandemic. Providing manual therapy to lower limbs is not an easy task and, in most cases, it involves multiple persons. Moreover, it is a monotonous job, and the service providers need to be in close contact with the patient thereby creating the risk of infection. In this circumstance, robot-assisted rehabilitation exercise for lower limbs offers a risk-free solution. This paper presents dynamic modeling and control simulation of One Degree of Freedom robotic chair-arm (robotic arm attached with a special chair). The control structure is designed with two compensators for position and velocity control. The simulation results show that the proposed system has a good potential in providing automatic rehabilitation therapy for lower limbs, especially for knee joint range of motion exercise. The results also indicate faster responses with settling time less than 0.04 second and steady-state error below 0.05. The findings show that a robotic chair arm can be used for providing automatic therapy to patients in situations like COVID-19 pandemic.